Effects of seeding date and seeding rate on yield, proximate composition and total tannins content of two Kabuli chickpea cultivars - Ruggeri, Roberto; Primi, Riccardo; Danieli, Pier Paolo; Ronchi, Bruno; Rossini, Francesco (Italian Journal of Agronomy, 2017)
Experiments were conducted in open field to assess the effect of seeding season and density on the yield, the chemical composition and the accumulation of total tannins in grains of two chickpea (Cicer arietinum L.) cultivars (PasciÃ  and Sultano). Environmental conditions and genetic factors considerably affected grain yield, nutrient and total tannins content of chickpea seeds, giving a considerable range in its qualitative characteristics. Results confirmed cultivar selection as a central factor when a late autumn-early winter sowing is performed. In effect, a more marked resistance to Ascochyta blight (AB) of Sultano, allowed better agronomic performances when favourable-to-AB climatic conditions occur. Winter sowing appeared to be the best choice in the Mediterranean environment when cultivating to maximise the grain yield (+19%). Spring sowing improved crude protein (+10%) and crude fibre (+8%) content, whereas it did not significantly affect the accumulation of anti-nutrients compounds such as total tannins. The most appropriate seeding rate was 70 seeds mâ€“2, considering that plant density had relatively little effect on the parameters studied.